2020
DOI: 10.1111/pace.14013
|View full text |Cite
|
Sign up to set email alerts
|

Thirty‐day readmissions after atrial fibrillation catheter ablation in patients with heart failure

Abstract: Background Randomized clinical trial data have demonstrated catheter ablation (CA) as a viable treatment modality for atrial fibrillation (AF). Patients with heart failure (HF) undergoing AF CA appear to derive improvements in quality of life and mortality compared to those treated with medical therapy (MT). Contemporary national data on 30‐day readmissions after CA compared to MT among patients with HF are lacking. Methods From the 2016 Nationwide Readmissions Databases, 749 776 (weighted national estimate: 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Lima et al recently described a significant reduction in 30-day readmissions (16.8% vs. 18.8%, p = .02) in patients with HF undergoing CA for AF compared with a propensity score matched group receiving medical therapy. 21 Importantly, although the costs of the index hospitalization were significantly higher for the CA group, after readmission, overall costs were similar between the two groups. Field et al found significant reductions in AF-related hospitalizations (64%), emergency department 22 visits (51%), and HF related hospitalizations (22%), all of which translated into a reduction in AF related costs and ED related costs.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Lima et al recently described a significant reduction in 30-day readmissions (16.8% vs. 18.8%, p = .02) in patients with HF undergoing CA for AF compared with a propensity score matched group receiving medical therapy. 21 Importantly, although the costs of the index hospitalization were significantly higher for the CA group, after readmission, overall costs were similar between the two groups. Field et al found significant reductions in AF-related hospitalizations (64%), emergency department 22 visits (51%), and HF related hospitalizations (22%), all of which translated into a reduction in AF related costs and ED related costs.…”
Section: Discussionmentioning
confidence: 89%
“…Finally, significant cost reductions could result from AF CA in HF patients. Lima et al recently described a significant reduction in 30‐day readmissions (16.8% vs. 18.8%, p = .02) in patients with HF undergoing CA for AF compared with a propensity score matched group receiving medical therapy 21 . Importantly, although the costs of the index hospitalization were significantly higher for the CA group, after readmission, overall costs were similar between the two groups.…”
Section: Discussionmentioning
confidence: 96%
“…Lima et al recently described a significant reduction in 30-day readmissions (16.8% vs 18.8%, P = 0.02) in patients with HF undergoing CA for AF compared with a propensity score matched group receiving medical therapy. 21 Importantly, although the costs of the index hospitalization were significantly higher for the CA group, after readmission, overall costs were similar between the two groups. Field et al found significant reductions in AF-related hospitalizations (64%), emergency department 22 visits (51%), and HF related hospitalizations (22%), all of which translated into a reduction in AF related costs and ED related costs.…”
Section: Discussionmentioning
confidence: 89%
“…In a propensity‐matched comparison of HF patients undergoing AF ablation versus those treated medically, ablation was associated with an 11% reduction in the 30‐day hospitalization rate ( p = .020) among all HF patients 73 and a reduction in the 120‐day hospitalization rate of 25.2% in HFrEF patients and 28.5% in HFpEF patients ( p < 0001), 66 resulting in a 20% RR in total hospitalization costs after ablation 66 . Similarly, in the Optum database, AF ablation was associated with a 64% reduction in AF‐related admissions, a 65% reduction in LOS, a 52% reduction in the need for cardioversions, a 51% reduction in ER visits, and a 22% reduction in HF admissions resulting in an overall 36% reduction in costs ( p < .0001) 74 …”
Section: Additional Considerationsmentioning
confidence: 99%